CYBERSECURITY: HOW TO TAKE MEASURES TO PROTECT YOUR INFORMATION ASSETS - Armas, Jimmy A. (2020)
With the implementation of new trends and the impact of digitization, mass data storage represents an appealing target for cyber attackers. This forces organizations to rethink and protect technological processes from a cybersecurity perspective. It is important to know what these threats are, and the basic steps to reduce the risk of being victims of a cyberattack